(untitled) (Research, Society and Development, 2022)
This study aimed to analyze the practices (participant observation) and narratives (interviews) of health and administrative professionals of a hospital, in necessity for hand hygiene in the hospital environment. This is a qualitative, descriptive, exploratory study of an analytical nature, using content analysis for the empirical material and the social theory representations (STR), using out twenty-one professionals (doctors, nurses, nursing technicians, physiotherapists, stretchers and administrators of health units). For data collection, 60 hours of participant observation and twenty-one interviews were used. The results showed that two categories: act of hand hygiene – perception of the dirty and clean and the needs of hand hygiene in the work environment. The study showed that hand hygiene seems to be a difficult habit to change and this study shows that most health professionals sanitize their hands according to their needs, that is, when they have the perception that their hands are really dirty or on occasions he had contact with the dirty, failing to do so at the recommended times. Despite the evidence of its effectiveness, compliance with hand hygiene is quite low, as verified in the participant observation, this may be due to the nature of hand hygiene being an action, driven by social behavior.